CYTOLOGIC DIAGNOSIS AND TREATMENT OF FELINE SPOROTRICHOSIS: CASE REPORT - Cagnini, Didier Quevedo; Rodrigues, Marcela Marcondes Pinto; Palumbo, Mariana Isa Poci; Heckler, Marta Cristina Thomas; Peixoto, Anaiara Silgueiro; Amorim, Renée Laufer; Machado, Luiz Henrique de Araújo (Veterinária e Zootecnia, 2023)
Sporotrichosis is a mycotic disease of humans and animals caused by a dimorphic fungus called Sporothrix schenckii. Domestic animals, particularly cats, play an important role for human infections. The diagnosis of sporotrichosis can be made by using cytologic and histopathologic examination, culturing the fungus, immunofluorescence or molecular methods. This paper describes the cytologic diagnosis by fine-needle aspiration and treatment of a case of feline sporotrichosis.